A putative ATP/GTP binding protein affects Leishmania mexicana growth in insect vectors and vertebrate hosts - Ishemgulova, Aygul; Kraeva, Natalya; Hlaváčová, Jana; Zimmer, Sara L; Butenko, Anzhelika; Podešvová, Lucie; Leštinová, Tereza; Lukeš, Julius; Kostygov, Alexei Yu; Votýpka, Jan; Volf, Petr; Yurchenko, Vyacheslav (PLoS neglected tropical diseases, 2017)
BACKGROUND: Leishmania virulence factors responsible for the complicated epidemiology of the various leishmaniases remain mainly unidentified. This study is a characterization of a gene previously identified as upregulated in two of three overlapping datasets containing putative factors important for Leishmania's ability to establish mammalian intracellular infection and to colonize the gut of an insect vector. METHODOLOGY/PRINCIPAL FINDINGS: The investigated gene encodes ATP/GTP binding motif-containing protein related to Leishmania development 1 (ALD1), a cytosolic protein that contains a cryptic ATP/GTP binding P-loop. We compared differentiation, growth rates, and infective abilities of wild-type and ALD1 null mutant cell lines of L. mexicana. Loss of ALD1 results in retarded growth kinetics but not defects in differentiation in axenic culture. Similarly, when mice and the sand fly vector were infected with the ALD1 null mutant, the primary difference in infection and colonization phenotype relative to wild type was an inability to achieve maximal host pathogenicity. While ability of the ALD1 null mutant cells to infect macrophages in vitro was not affected, replication within macrophages was clearly curtailed. CONCLUSIONS/SIGNIFICANCE: L. mexicana ALD1, encoding a protein with no assigned functional domains or motifs, was identified utilizing multiple comparative analyses with the related and often experimentally overlooked monoxenous flagellates. We found that it plays a role in Leishmania infection and colonization in vitro and in vivo. Results suggest that ALD1 functions in L. mexicana's general metabolic network, rather than function in specific aspect of virulence as anticipated from the compared datasets. This result validates our comparative genomics approach for finding relevant factors, yet highlights the importance of quality laboratory-based analysis of genes tagged by these methods.
Keywords: Virulence; Animals; Leishmania mexicana; protozoální proteiny; Female; leishmanióza kožní; Insect Vectors; Gene Expression Regulation, Developmental; makrofágy; ženské pohlaví; Protozoan Proteins; proteiny vázající GTP; GTP-Binding Proteins; Macrophages; Mice; Mice, Inbred BALB C; Psychodidae; myši; Leishmaniasis, Cutaneous; virulence; hmyz - vektory; myši inbrední BALB C; zvířata; vývojová regulace genové exprese